Strategy for Strengthening Waqf Administration at the KUA: Mitigating the Risk of Disputes and Asset Takeover by Heirs - Magfirah (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
Waqf assets in Indonesia currently face high risks of disputes and takeovers by heirs due to weak formal legal administration at the Office of Religious Affairs (KUA) level. This policy paper aims to formulate a strategic framework for strengthening administrative governance to ensure legal certainty and protect community assets from the permanent loss of benefits. The policy methodology employs a descriptive-qualitative analysis with a literature study approach and policy evaluation grounded in William N. Dunn’s theory. Problems are prioritized through the Urgency, Seriousness, and Growth (USG) matrix, followed by a scoring analysis of policy alternatives based on criteria of effectiveness, efficiency, adequacy, equity, responsiveness, and feasibility. The analysis identifies that the root causes stem from vulnerable manual record-keeping systems and low legal literacy among waqf managers. As a strategic solution, two primary policy recommendations are proposed to the Minister of Religious Affairs: first, the reinforcement of digitalization regulations through the implementation of the Electronic Waqf Pledge Deed (E-AIW), integrated nationally with the land registry system; second, the instruction of a proactive